Gerakan Hidup Sehat Sejak Dini: Edukasi Aktivitas Fisik Dan Pola Hidup Aktif Bagi Siswa SD - Muh Ali Akbar; Iyan Nurdiyan Haris; Harry Syahputra Nasution; Ayu Purnama Wenly; Andi Amry Yahya; Ernawati Ernawati (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2026)
The low level of physical activity among elementary school students in Kolaka Regency poses a potential risk to children’s health and overall development. This community service program aimed to improve students’ knowledge and active lifestyle behaviors through educational interventions and the habituation of physical activity. The program was implemented over a two-month period using an educational, participatory, and practical approach, which included health education sessions, game-based physical activity practices, and the implementation of daily movement routines at school. Evaluation was conducted through pre-test and post-test assessments, as well as observations of student participation. The results indicated a significant improvement in students’ knowledge, as reflected in the comparison between pre-test and post-test scores, along with increased participation in daily physical activities. The habituation of regular physical activity also contributed to the development of active lifestyle behaviors among students. This program contributes to enhancing awareness of healthy living and has the potential to serve as a practical and scalable intervention model for elementary schools.